"Resilience" as a policy keyword: Arts Council England and austerity. (4th March 2022) - Gupta, Suman; Gupta, Ayan-Yue
ABSTRACT: This article examines how "resilience" appeared and became embedded as a keyword in Arts Council England's (ACE) policy discourse from 2010, initially in response to the financial crisis in Britain and the government's call for austerity. The general dynamic of what we call policy keywords here is thereby exemplified, while throwing light on Arts policy making at a specific historical juncture in Britain. Some of the features of such policy keywords are considered here: in terms of connotative ambiguities and associations, definitions, and naming or branding practices. Their distinctive purchase in ACE's "resilience" policies is analysed in the process. The policies were designed to reduce public spending by appealing to normative agendas which, in this instance, seemed contingent on a larger and immediate impetus and were derived from the field of "ecological economics".